Financial Management and Control Assessment Tool for Local Government Authorities - Provazníková, Romana; Rudnitska, Ruslana (Vysoká škola báňská-Technická univerzita Ostrava, 2021)
The aim of developing new Financial management and control (FMC) Assessment Tool for Local Government Authorities is strengthening of local government financial and general management and ensuring that the operational and financial relations between central and local government are compatible with securing the central government objectives. The paper presents the author's approach to the development and adaptation of FMC assessment tools to the local government authority needs. The development of a mechanism for evaluating the effectiveness of the FMC-system at the local level performs the number of important functions, among which the authors singled out: reducing information asymmetry by providing reliable and comprehensive information, protecting the property and documents, ensuring effective economic performance, observation of accounting principles and presentation of reliable financial records, obeying laws and executive acts, implementation of the effective system of risk control. The authors proposed such elements of FMC assessment for local government authority as Questionnaire for Senior Management; FMC benchmark criteria; Assessment Questions regarding relation local body and subordinated/related bodies; Questionnaire for preliminary assessment phase; Interview questions. The combination of instruments depends mostly on the scope of assessment.
Finanční řízení a hodnotící nástroje pro místní samosprávu.
Keywords: budgetary policy; financial management and control; local government authority; public finances; rozpočtová politika; finanční řízení a kontrola; místní samosprávy; veřejné finance